Primal fear - Diehl, William (New York : Villard Books, 1993)
A Chicago archbishop is savagely murdered, a knife-wielding young man swears that he is innocent, and a brilliant renegade defense lawyer battles to uncover the truth behind the murder.
National College of Business and Arts
Keywords: Bishops -- Fiction; Detective and mystery fiction